The Frequency Of Attention Deficit Hyperactivity Disorder Among School Age Children Of Rawalpindi - Maimoona Maheen, Mehak Ruqia, Muzna Mehmood, Maimoona Maheen, Mehak Ruqia, Muzna Mehmood (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Attention deficit hyperactivity disorder (ADHD) is mainly defined by features of inattention, hyperactivity, and impulsivity. It is the most frequently encountered childhood-onset neurodevelopmental disorder in the primary care settings. Objective: The objective of this study is to determine the prevalence of Attention Deficit Hyperkinetic Disorder (ADHD) in school going children of Rawalpindi. Methods: This descriptive cross-sectional study was carried out from May 2017 to July 2018 in schools of Rawalpindi. Our study population comprised of children and teens with age ranging from 6-16. A standard questionnaire ‘Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition Teachers’ Version’ (DSM-IV-TR) was used to collect information from 223 teachers about the children. Results: Out of 223 study subjects, 105 (47.0%) were male and 118 (52.9%) were females with mean age of 12 years. Out of the total sample, 77 (34.5%) were diagnosed with ADHD. Out of these 77, we found out that 41 (53.2%) were suffering from ADHD-I (inattention) making it the most prevalent sub-type of the ADHD in the given sample, whereas 18 (23.3%) children were found out to be suffering from ADHD-HI (hyperactivity) and 18 (23.3%) from ADHD-C (combined) type. Conclusion: The prevalence of ADHD is much higher in our population than in most regions of the world indicating negligence towards this important psychiatric problem.